Eksplorasi Teknologi Pendukung Data Science untuk Industri Unggulan di Wilayah Kota Surabaya dan Sekitarnya - Tanamal, Rinabi; Soekamto, Yosua Setyawan; Wiradinata, Trianggoro (Teknik Informatika Universitas Pamulang, 2021)
Data science competence is still quite uncommon for most people, even though this competence is very important in managing business development strategies in various leading industrial fields. Through data science, companies can find patterns, perform clustering, calculate predictions more accurately to make decisions that have an impact on company excellence. Lack of knowledge about data science, researchers seek firstly in the industry to explore tools that are mostly used, convenience, challenges, measuring success tools and advantages. In this study, the researchers conducted a Focus Group Discussion by interviewing resource persons who worked as Data Scientists. Interview method to discuss aspects of Demographics, aspects of Technology-Task Fitness, and aspects of the Technology Acceptance Model. The results of this study conclude that the tools that are the mainstay of the industry in Surabaya and its surroundings area are Jupyter Notebook, Python, and Tableau. The success in using these tools still depends on the user's abilities, the results of user simulations, team discussions, and the evaluation process.